Budaya Hukum Dan Dinamika Kepatuhan Masyarakat Melalui Pendekatan Sosio-Legal Mikro Dan Makro - Nuraini Astrid (Universitas Sains dan Teknologi Komputer, 2025)
This study examines legal culture and the dynamics of public compliance through an integrated socio-legal approach that bridges micro-level individual experiences and macro-level institutional structures. Departing from fragmented analyses that treat compliance either as an individual attitude or an institutional outcome, this research employs a qualitative, multilevel design combining in-depth interviews, limited observation, and document analysis to capture the relational processes through which legal compliance is produced and negotiated. The findings demonstrate that compliance is not primarily driven by coercive enforcement or formal regulation, but by perceptions of procedural justice, institutional consistency, and the quality of everyday interactions between citizens and legal authorities. Legal culture emerges as a dynamic, relational process in which individual experiences shape institutional legitimacy, while institutional practices simultaneously condition public trust and behavioral responses to the law. By conceptualizing legal culture as a multilevel socio-legal process, this study contributes to the literature by advancing an integrative analytical framework that moves beyond the micro–macro divide and offers theoretical and practical insights for designing legitimacy-oriented legal governance and sustainable compliance strategies.